An Analytical Study for Validation and Standardization of Vati. - Sharma, Jagriti; Swami, Pooja (International Research Journal of Ayurveda & Yoga, 2023)
Introduction-Traditional medicine has a long history of serving people all over the world. Today the world is looking towards the Ayurveda with great hope and faith. With these new challenges emerges in the form of queries of the modern man who would have a right to know about the drug he is consuming. To meet this new trust of inquisitiveness, standard of drugs of Indian System of Medicine is mandatory. In the process of assurance, to ascertain the prepared product is full proof and without any defects, these prepared products need to undergo several analytical parameters concerned to them and get clearance. This article is a step to standardized and validate the ayurvedic formulation through analytical study. Material and methods- The drugs selected for study are one of the mahakashaya Dasemani – Angamardha Prashaman Dasemani described in Charak Samhita Sutra Sthan and Bhagottar Gutika a Herbo- mineral formulation is from Bhaishajya Ratnavali. The various parameters studies are or organoleptic characters, physicochemical parameters of vati like disintegration, friability, loss on drying, acid insoluble ash, water soluble ash etc. and microbial contamination. Results – All the parameters studied are within the limits and hence validate the safely and effectively use of vati. Conclusion Analytical study of a product provides standards to judge its quality. It is useful to decide future work plan and objective parameters to know the exact status of drug by conducting the comparative study of various samples during drug preparation.